Optimizing Solvent-Assisted SAGD in Deep Extra-Heavy Oil Reservoirs: Mechanistic Insights and a Case Study in Liaohe - Ying Zhou; Siyuan Huang; Simin Yang; Qi Jiang; Zhongyuan Wang; Hongyuan Wang; Lifan Yue; Tengfei Ma (Energies)
This study investigates the feasibility and optimization of Expanding Solvent Steam-Assisted Gravity Drainage (ES-SAGD) in deep extra-heavy oil reservoirs, with a focus on the Shu 1-38-32 block in the Liaohe Basin. A modified theoretical model that accounts for steam quality reduction with increasing reservoir depth was applied to evaluate SAGD performance. The results demonstrate that declining steam quality at greater burial depths significantly reduces thermal efficiency, the oil–steam ratio (OSR), and overall recovery in conventional SAGD operations. To overcome these challenges, numerical simulations were conducted to evaluate the effect of hexane co-injection in ES-SAGD. A 3 vol% hexane concentration was found to improve oil recovery by 17.3%, increase the peak oil production rate by 36.5%, and raise the cumulative oil–steam ratio from 0.137 to 0.218 compared to conventional SAGD. Sensitivity analyses further revealed that optimal performance is achieved with cyclic injection during the horizontal expansion stage and chamber pressures maintained above 3 MPa. Field-scale forecasting based on five SAGD well pairs showed that the proposed ES-SAGD configuration could enhance the cumulative recovery factor from 28.7% to 63.3% over seven years. These findings clarify the fundamental constraints imposed by steam quality in deep reservoirs and provide practical strategies for optimizing solvent-assisted SAGD operations under such conditions.